Effect of Teriparatide on Bone Mineral Density and Trabecular Bone Score in Type 2 Diabetic Patients with Osteoporosis: A Retrospective Cohort Study - Chihiro Munekawa; Yoshitaka Hashimoto; Noriyuki Kitagawa; Takafumi Osaka; Masahide Hamaguchi; Michiaki Fukui (Medicina, 2022)
The BMDs of the lumbar spine, whole femur, and femoral neck and TBS were measured. Change in BMD or TBS was defined as the BMD or TBS at follow-up, performed 1 year after baseline, minus baseline BMD or TBS. Results: This retrospective cohort study included 93 patients, of whom 52 received no medication, 26 received bisphosphonates, and 15 received weekly teriparatide. BMD of the lumbar spine increased in all three groups. There was no change in BMD of the whole femur and femoral neck in the no medication and bisphosphonates groups, whereas the BMD of the whole femur (from 0.73 (0.15) to 0.74 (0.15) g/cm2, p = 0.011) and femoral neck (from 0.59 (0.16) to 0.60 (0.16) g/cm2, p = 0.011) in the teriparatide group increased. The change in BMD of the femoral neck (no medication; −0.002 (0.034) g/cm2, bisphosphonates; −0.0001 (0.024) g/cm2, and teriparatide; 0.017 (0.022) g/cm2, p = 0.091) or TBS (no medication; −0.007 (0.051), bisphosphonates; −0.058 (0.258), and teriparatide; 0.021 (0.044), p = 0.191) in the teriparatide group tended to be higher than that in the other groups, although there was no statistically significant difference. Conclusions: Teriparatide increased the BMD of the femoral neck and TBS in osteoporosis patients with type 2 diabetes mellitus, compared to bisphosphonates and no medication.